2007
DOI: 10.1093/aje/kwm157
|View full text |Cite
|
Sign up to set email alerts
|

Association of Oral Contraceptive Use, Other Contraceptive Methods, and Infertility with Ovarian Cancer Risk

Abstract: Although oral contraceptives are protective for ovarian cancer, it is unclear how long this protection persists. The authors prospectively assessed this question as well as associations of other, less studied contraceptive methods (tubal ligation, rhythm method, diaphragm, condoms, intrauterine device, foam, spousal vasectomy) and infertility with ovarian cancer risk among 107,900 participants in the US Nurses' Health Study. During 28 years of follow-up (1976-2004), 612 cases of invasive epithelial ovarian can… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
95
2
2

Year Published

2008
2008
2013
2013

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(105 citation statements)
references
References 44 publications
6
95
2
2
Order By: Relevance
“…We identified those risk factors to be considered: parity, oral contraceptive use, breastfeeding, tubal ligation, painful periods or endometriosis, obesity or polycystic ovarian syndrome, and talc use. These risk factors are concordant with published epidemiologic data related to reproductive factors, [15][16][17][18][19][20][21][22][23] use of talc, [17][18][19] tubal ligation, 20,24-27 endometriosis, 28 and polycystic ovarian syndrome or obesity. 29,30 It is also known that approximately 2% of Jewish women carry one of three founder mutations of BRCA1 or BRCA2.…”
Section: Discussionsupporting
confidence: 89%
“…We identified those risk factors to be considered: parity, oral contraceptive use, breastfeeding, tubal ligation, painful periods or endometriosis, obesity or polycystic ovarian syndrome, and talc use. These risk factors are concordant with published epidemiologic data related to reproductive factors, [15][16][17][18][19][20][21][22][23] use of talc, [17][18][19] tubal ligation, 20,24-27 endometriosis, 28 and polycystic ovarian syndrome or obesity. 29,30 It is also known that approximately 2% of Jewish women carry one of three founder mutations of BRCA1 or BRCA2.…”
Section: Discussionsupporting
confidence: 89%
“…The possible link between exposure to ovulation induction drugs and ovarian cancer development has biological credibility, given that "incessant ovulation" and associated alternation in endogenous hormones during reproductive years are plausible explanations for several factors that alter ovarian cancer risk [1,9,10]. This association was investigated in numerous case-control [11][12][13][14][15][16][17][18] and cohort studies [7,8,[19][20][21][22][23][24][25][26][27][28][29][30]. As for invasive ovarian cancer development, all but one case-control study [11] failed to demonstrate a significant excess risk of invasive ovarian cancer following treatments for infertility.…”
Section: Ovarian Cancermentioning
confidence: 99%
“…In a recent update from the Nurses Health Study, Tworoger et al [9 ] found that women who used oral contraceptives for more than 5 years had a reduced risk of ovarian cancer (rate ratio 0.58; 95% CI, 0.39-0.87), whereas a 38% reduction in incident ovarian cancer risk was observed with at least 10 years of oral contraceptive use. This protective effect attenuates after 20 years since last use.…”
Section: Incessant Ovulation As a Risk Factor For Ovarian Cancermentioning
confidence: 99%